Pengaruh Harga Promosi Dan Lokasi Terhadap Keputusan Konsumen Pada Pembelian Di Giant Ekstra Balikpapan - Ridianti, Rita; Putri Cipto, Rahajeng Cahyaning (Arthavidya Jurnal Ilmiah Ekonomi, 2018)
ABSTRACT. This study aimed to examine the effect of the price, promotion and location of the consumers decision to shop in Giant Extra Balikpapan. Type of research use is descriptive quantitative and data sources use is type of data primary to 90 responden.Based on test result regresi linear berganda, price, promotion and location on simultan of the consumers decision to shop amount 11,552. The test parsial variable price and promotion give signifikan effect of the consumers decision to shop amount 2,316 and 3,643.And then variable location not give signifikan effect of the consumers decision amount 0,33.The Giant Extra Balikpapan, will be keep price and promotion Key words: price, promotion, location, consumers decision.